2012
DOI: 10.1681/asn.2011100967
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence Limits Regenerative Capacity and Allograft Survival

Abstract: Long-term graft survival after kidney transplantation remains unsatisfactory and unpredictable. Interstitial fibrosis and tubular atrophy are major contributors to late graft loss; features of tubular cell senescence, such as increased p16INK4a expression, associate with these tubulointerstitial changes, but it is unknown whether the relationship is causal. Here, loss of the INK4a locus in mice, which allows escape from p16 INK4a -dependent senescence, significantly reduced interstitial fibrosis and tubular at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
150
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(158 citation statements)
references
References 40 publications
6
150
0
2
Order By: Relevance
“…In addition, decreased serum levels of renal-derived Klotho (20) might also have systemic and renal adverse consequences considering its pleiotropic functions including cytoprotection (27), preservation of endothelial function (28), inhibition of fibrosis (21,29). Klotho has also antioxidant, anti-inflammatory, and anti-senescence functions (12), that might support the regeneration of TEC maintaining nephron integrity (10,30). In conclusion, our data demonstrate for the first time a direct involvement of complement in Klotho down-regulation in IRI.…”
Section: Complement Modulation Of Klothomentioning
confidence: 99%
“…In addition, decreased serum levels of renal-derived Klotho (20) might also have systemic and renal adverse consequences considering its pleiotropic functions including cytoprotection (27), preservation of endothelial function (28), inhibition of fibrosis (21,29). Klotho has also antioxidant, anti-inflammatory, and anti-senescence functions (12), that might support the regeneration of TEC maintaining nephron integrity (10,30). In conclusion, our data demonstrate for the first time a direct involvement of complement in Klotho down-regulation in IRI.…”
Section: Complement Modulation Of Klothomentioning
confidence: 99%
“…3 All of the aforementioned analyses were performed by blinded observation of 12 random nonoverlapping visual fields (2003 magnification). Glomeruli and vessels larger than the size of adjacent tubules were not included in the analysis.…”
Section: Renal Histology and Immunohistochemistrymentioning
confidence: 99%
“…1 Among the involved mechanisms, cellular senescence has emerged as an important factor disturbing renal regeneration and promoting kidney aging. [2][3][4][5] Cellular senescence is a state of irreversible growth arrest resulting from telomere dysfunction or various cellular stresses that activate cyclin-dependent kinase inhibitors, particularly p16 INK4a . We have previously shown that ischemia/ reperfusion (I/R) -related cell stress enhances the expression of p16…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 In support of this view, we have observed that experimental ablation of p16 INK4a -driven senescence leads to a favorable outcome after AKI and to improved graft survival. 13 Most recently, Baker and colleagues have shown that clearance of p16…”
Section: Introductionmentioning
confidence: 99%